Antimicrobial and antibiofilm potential of Curcuma longa Linn. Rhizome extract against biofilm producing Staphylococcus aureus and Pseudomonas aeruginosa isolates - Suwal, Newton; Subba, Romit Kumar; Paudyal, Prem; Khanal, Dharma Prasad; Panthi, Mamata; Suwal, Neelam; Nassan, Mohamed A.; Alqarni, Mohammed; Batiha, Gaber El-Saber; Koirala, Niranjan (Cellular and Molecular Biology, 2021)
More than 65% of all human bacterial infection are associated with biofilm. Bacteria in such biofilms are 10 to 1000-fold more resistant to antibiotics than free living bacteria cells. Organisms such as S. aureus and P. aeruginosa are responsible for a significant number of biofilm related infections. In this study, we investigated the antimicrobial and anti-biofilm activity of C. longa L. rhizome extract against biofilm producing S. aureus and P. aeruginosa isolates. The results of MIC and MBC demonstrated promising antibacterial activity of the rhizome extract. TLC and column chromatography detected various curcuminoids while phytochemical analysis also reveals presence of number of bioactive compounds such as alkaloids, flavonoids, phenolics, terpenoids, etc. Micro titer plate assay indicated significant inhibition of biofilm formation in clinical isolates treated with turmeric extract. Thus, on basis of our results turmeric extracts can be considered as natural antibiofilm and antibacterial agent.